Peran Madrasah Diniyah Dalam Upaya Pengembangan Karakter Anak di Desa Jlumpang Kecamatan Bancak Kabupaten Semarang - Suryani, Dina Tri; Nurharini, Atip; Sari, Rikha Permata; Musyarofah, Musta’inatul; Al Faris, Muhammad Rafli (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to determine the role of Madrasah Diniyah in efforts to develop children's character in Jlumpang Village, Bancak District, Semarang Regency. This research uses a qualitative descriptive research type. The data collection techniques used are filling out questionnaires, observation and literature study to obtain data about how children's characters are developed. This research involved teachers who taught at Madrasah Diniyah in Jlumpang Village, Bancak District, Semarang Regency as samples. The research results show that Madrasah Diniyah has a very important role in developing children's character, both religiously and personally. This cannot be separated from the role of education which always shapes and directs them in their daily lives. Education in schools, families and the community are supporting factors in developing student character. In conclusion, Madrasah Diniyah plays an important role in developing children's character, and this role can be enhanced with good cooperation between Madrasah Diniyah, families and the community.